READING THE MUSEUM ANGKUT: CULTURAL SPACE PRODUCTION AND EXHIBITION NARRATIVE - Nindyo Budi Kumoro; Irsyad Martias; Manggala Ismanto; Hipolitus Kristoforus Kewuel; Andi Azmi Saifullah; Jihananda Marcel Egidyah (Universitas Padjadjaran, 2020)
This article is a museum study from an anthropological perspective. Generally, the museum is an institution that stores and preserves particular material cultures. On the other side, a museum can also be critically seen as a space for the production of cultural discourse that narrates a particular ideology through exhibition strategies and display systems. This study wants to explore the discourse of cultural ideology that is represented by the museum through the design and exhibition. The museum is no longer only monopolized by the state but also developed by the private sector which offers a fusion model between the museum, edutainment, and amusement park. Thus, this article proposes a case study of the Museum Angkut in Batu, East Java, one of the most popular private museums in Indonesia that exhibits transportation system and world civilization themes assembled by implementing amusement park concepts. This article would like to address the issue of the production of cultural discourse. The research questions are what kind of cultural discourse production is narrated in the Museum Angkut, and how has it been materialized through the display strategy? Additionally, this article explores the relationship of the visitor with material objects in the museum. This paper uses a hermeneutic approach, and Michael Foucault’s heterotopia to examine how cultural imagination with its ideology is represented in museum bodies. As a result, we argue that the Museum Angkut can reflect the character of society, as a post-colonial nation in the sense of seeing self and other cultures.